Analysis of Hepatitis B Virus Haplotype Diversity Detects Striking Sequence Conservation Across Genotypes and Chronic Disease Phase. Issue 5 (29th April 2021) - Wagner, Josef; Yuen, Lilly; Littlejohn, Margaret; Sozzi, Vitina; Jackson, Kathy; Suri, Vithika; Tan, Susanna; Feierbach, Becket; Gaggar, Anuj; Marcellin, Patrick; Buti Ferret, Maria; Janssen, Harry L.A.; et al.
Abstract : Background and Aims: We conducted haplotype analysis of complete hepatitis B virus (HBV) genomes following deep sequencing from 368 patients across multiple phases of chronic hepatitis B (CHB) infection from four major genotypes (A‐D), analyzing 4, 110 haplotypes to identify viral variants associated with treatment outcome and disease progression. Approach and Results: Between 18.2% and 41.8% of nucleotides and between 5.9% and 34.3% of amino acids were 100% conserved in all genotypes and phases examined, depending on the region analyzed. Hepatitis B e antigen (HBeAg) loss by week 192 was associated with different haplotype populations at baseline. Haplotype populations differed across the HBV genome and CHB history, this being most pronounced in the precore/core gene. Mean number of haplotypes (frequency) per patient was higher in immune‐active, HBeAg‐positive chronic hepatitis phase 2 (11.8) and HBeAg‐negative chronic hepatitis phase 4 (16.2) compared to subjects in the "immune‐tolerant, " HBeAg‐positive chronic infection phase 1 (4.3, P < 0.0001). Haplotype frequency was lowest in genotype B (6.2, P < 0.0001) compared to the other genotypes (A = 11.8, C = 11.8, D = 13.6). Haplotype genetic diversity increased over the course of CHB history, being lowest in phase 1, increasing in phase 2, and highest in phase 4 in all genotypes except genotype C. HBeAg loss by week 192 of tenofovir therapy was associated with different haplotype populations at baseline. Conclusions: Despite a degree of HBV haplotype diversity and heterogeneity across the phases of CHB natural history, highly conserved sequences in key genes and regulatory regions were identified in multiple HBV genotypes that should be further investigated as targets for antiviral therapies and predictors of treatment response.